Measuring Intergenerational Justice - Laurence J. Kotlikoff (Intergenerational Justice Review)
Concern with intergenerational justice has long been a focus of economics. This essay considers the effort, over the last three decades, to quantify generational fiscal burdens using label-free fiscal gap and generational accounting. It also points out that government debt -- the conventional metric for assessing generational fiscal justice,– has no grounding in economic theory. Instead, official debt is the result of economically arbitrary government labelling decisions: whether to call receipts “taxes” rather than “borrowing” and whether to call payments “transfer payments” rather than “debt service”. Via their choice of words, governments decide which obligations to put on, and which to keep off, the books. The essay also looks to the future of generational fiscal-justice analysis. Rapid computational advances are permitting economists to understand not just direct government intergenerational redistribution, but also how such policies impact the economy that future generations will inherit.